IMMOBILIZATION OF GLUCOSE OXIDASE ENZYME FROM Penicillium sp-3 LOCAL STRAIN - Ahyar Ahmad; Andi Syaiful; Firman AP Firman AP; Abdul Rauf Patong (Universitas Gadjah Mada, 2007)
Immobilization of glucose oxidase (GOD) enzyme from Penicillium sp-3 local strain has been carried out using ionotropically entrapping method in Ca-alginate membrane coupled with Na-polyacrilate. The entrapment of the enzyme in diffusion membrane occur spontaneously by cross-linking between Na-alginate/Na-polyacrilate and CaCl2. The GOD enzyme immobilizedby addition of 1 % Na-polyacrilate has the highest encapsulation efficiency, that is 87.13 % with the smallest percentage of diffusion, i.e. 23.37% and the relative activity of 50%. The GOD immobilized enzyme had good stability at the pH range 4 - 7 during 30 minutes of storage and was stable at a temperature of 20 oC. The activity of the GOD enzyme after being utilized continuously for 5 times only decrease up to 47,06 % compared to that in the initial utilization.